Effect of one time coffee fragrance inhalation on working memory, mood, and salivary cortisol level in healthy young volunteers: a randomized placebo controlled trial - Thaneeya Hawiset (Integrative Medicine Research)
Background: Olfactory system regulates the brain which controls emotional memory. Coffee is one of the most consumed beverages in the world. Drinking coffee shows beneficial effects for mood, memory, and psychomotor performance. This work aimed to determine the effects of inhaling coffee fragrance on memory, mood, and salivary cortisol level in healthy young volunteers. Methods: Eighty young males and females, aged between 18–22 years old, were randomly assigned into two groups: a placebo group inhaling scent from carbon powder and a coffee fragrance group inhaling coffee fragrance. Subjects were assigned to inhale either placebo or coffee fragrance for five minutes. Before and after inhalation period, the clinical assessments were assigned to each subject including computerized assessment battery test for cognitive performance, and self-related visual analogue mood scales for evaluation of mood score. The salivary cortisol level was assessed with cortisol ELISA kit. In addition, the blood pressure and heart rate were also evaluated. Results: Inhalation of coffee fragrance enhanced cognitive parameters, including continuity of attention, quality of memory, and speed of memory, and also increased the mood score of alertness. However, there were no significant changes in salivary cortisol level, blood pressure, and heart rate between pre-and post-inhalation. Conclusion: One time of coffee fragrance inhalation may enhance working memory and stimulates alertness. However, inhaling coffee fragrance does not reduce stress or modulate autonomic response to stress. Keywords: Coffee fragrance, Memory, Mood, Salivary cortisol level